2016
DOI: 10.1007/s00265-016-2251-7
|View full text |Cite
|
Sign up to set email alerts
|

Alternative reproductive tactics, sperm mobility and oxidative stress in Carollia perspicillata (Seba’s short-tailed bat)

Abstract: In social systems with alternative reproductive tactics, sneakers face a higher level of sperm competition than harem males and hence are predicted to allocate more resources to ejaculates. Antioxidants can protect sperm against oxidative stress, and thus, their allocation to the ejaculate may depend on mating tactic. In this study on the frugivorous bat Carollia perspicillata, we assessed, for harem and sneaker males, four sperm mobility traits, blood and ejaculate markers of the redox balance and the ejacula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 97 publications
(116 reference statements)
0
18
1
Order By: Relevance
“…According to Fasel et al (2016), the harem males father approximately 60% of the offspring in a given breeding season, whereas the remaining 40% are fathered by peripheral and bachelor males. Fasel et al (2017) found that sperm velocity and survival were lower in harem males than in sneaker (bachelor + peripheral) males of C. perspicillata. The authors did not associate testicle size with sperm quality measurements, but suggest that ejaculate volume was not statistically different between male mating tactics.…”
Section: Male Asymmetry and Sperm Competitionmentioning
confidence: 88%
See 2 more Smart Citations
“…According to Fasel et al (2016), the harem males father approximately 60% of the offspring in a given breeding season, whereas the remaining 40% are fathered by peripheral and bachelor males. Fasel et al (2017) found that sperm velocity and survival were lower in harem males than in sneaker (bachelor + peripheral) males of C. perspicillata. The authors did not associate testicle size with sperm quality measurements, but suggest that ejaculate volume was not statistically different between male mating tactics.…”
Section: Male Asymmetry and Sperm Competitionmentioning
confidence: 88%
“…Fasel et al. () found that sperm velocity and survival were lower in harem males than in sneaker (bachelor + peripheral) males of C. perspicillata . The authors did not associate testicle size with sperm quality measurements, but suggest that ejaculate volume was not statistically different between male mating tactics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such status-dependent investment, whereby males at the lower end of the social hierarchy (e.g. satellite or sneaker males) exhibit better sperm performance than dominant males, has been observed in captive and wild vertebrates (Stockley et al, 1994;Froman et al, 2002;Neff et al, 2003;Fitzpatrick et al, 2007;Fasel et al, 2016). Similarly, in house sparrows, which display a linear hierarchy, males at the top and males at the bottom of the hierarchy have been found to produce lower quality ejaculates than males in the middle of the hierarchy (Rojas Mora et al, 2017a).…”
Section: Introductionmentioning
confidence: 80%
“…Under risk of sperm competition, males might trade-off resources between traits that reduce sperm competition (e.g., increased mate guarding) versus traits that increase fertilization success (e.g., increased sperm quality, Kelly & Jennions, 2011;Schradin, Eder, & Müller, 2012). Such statusdependent investment, where non-mate-guarding floater, satellite, or sneaker males exhibit better sperm performance than dominant mateguarding males, has been observed in captive and wild vertebrates (Fasel et al, 2016;Fitzpatrick, Desjardins, Milligan, Montgomerie, & Balshine, 2007;Froman, Pizzari, Feltmann, Castillo-Juarez, & Birkhead, 2002;Neff, Fu, & Gross, 2003;Stockley, Searle, Macdonald, & Jones, 1994). Therefore, effects of individual social status should also be estimated when quantifying sperm performance in systems with statedependent plasticity in tactics.…”
mentioning
confidence: 99%